Realization of a Second Harmonic Antenna for Rural Communications* - Adit Kurniawan; Ahmad Hasyim; Yuyu Wahyu (Institute for Research and Community Services, Institut Teknologi Bandung, 2006)
In this research, an active antenna operated at the second harmonic frequency is investigated, and is implemented using microstrip antenna material. The antenna consists of a FET oscillator which plays as a fundamental frequency oscillator and a frequency multiplier, and a patch antenna resonated at the second harmonic frequency as the radiator. A maximum second-harmonic output power can be extracted when the load impedance of the oscillator is optimized both at the fundamental and at the second harmonic frequencies. A rectangular patch antenna is used to radiate the second harmonic output power from the oscillator. The patch impedance is matched resistively at the second harmonic frequency. The patch antenna is fabricated using Diclad 522 microstrip substrates (relative permitivity ï¥r = 2.5) with a dielectric thickness of 1.57 mm. A GaAs FET AT-8250 transistor is used as an oscillator and a frequency multiplier and acts as the active component. Fundamental frequency is designed at 2,4 GHz band, so that the second harmonic frequency operates at 4,8 GHz band. The frequency is chosen to facilitate and to extend the needs of communications in rural areas using the unlicensed Industrial Scientific, and Medical (ISM) band. Operating the communication infrastructures intended for the use at 2.4 GHz band at its second harmonic frequency, is intended to alleviate interference levels at 2.4 GHz.